Influence of Cryptocurrency on the Economy Of 5 ASEAN Country - Wahyu Ramdhani, Budi; Pawirosumarto, Suharno; Zainudin, Zalina (International Journal of Psychosocial Rehabilitation, 2020)
A cryptocurrency is a digital currency designed to work as a standard of exchange that uses cryptography for safekeeping (D’Alfonso, Langer, & Vandelis, 2016). In the world of cryptocurrency, there are over 800 types of cryptocurrencies for people to choose, but the most significant & widely used is Bitcoin. In 2008, Satoshi Nakamoto was first established the Bitcoin and Bitcoin is designed as a peer-to-peer network which prevents cash from double-spending (D’Alfonso et al., 2016). Bitcoin is a new form of secure currency that does not need a bank government agency or middleman to operate. As a result, it effects a monetary system which operates outside government regulation, threatens the consistency of financial systems and financial sovereignty of countries. It is a fully digital currency and to exchange bitcoins between computer a peer-to-peer network is required. The whole point is, it shares stuff by letting people make copies to download. The people with having system just carry out transaction among themselves what is called a decentralized network or blockchain. Blockchain uses to structure all the data, which allow the creation of decentralized digital ledgers where a person cannot hack another transaction. Furthermore, blockchain record all the transaction and act as an accounting system (Gandal & Halaburda, 2010).